Designing and implementation of a intensity based fiber optic vibration sensor - Abir, Md. Ridwan; Sarker, Mitalee (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.